THE MAIN CHALLENGES OF DUAL VOCATIONAL EDUCATION AND TRAINING SYSTEM TRANSFER - Лариса Гончар (National Academy of Educational Sciences of Ukraine, 2022)
Developing countries need practical VET systems that will meet the needs of the economic sector. Ukraine is making efforts to introduce a dual system of vocational education and training and has already faced many challenges in this process. This study highlights the difficulties faced by Ukraine during the implementation of the dual form in VET, and the problems of other countries in this process. The purpose of this study is the analysis of the main principles of the transfer of the dual VET form through the prism of the problems that Ukraine has faced. The study is based on such authentic sources as articles, international studies that made it possible to structure the knowledge base to describe the object of the study. The findings show that direct transfer or implementation poses numerous challenges and difficulties and shows that close cooperation between all stakeholders as well as shared awareness and commitment of all participants in education is paramount for successful VET transfer. It is concluded that it is necessary to clearly and systematically consider the issue of direct implementation of the German dual VET experience in another country with the obligatory preliminary study of specific challenges and specific resistance factors.